1992
DOI: 10.1128/jb.174.11.3549-3557.1992
|View full text |Cite
|
Sign up to set email alerts
|

Membrane intermediates in the peptidoglycan metabolism of Escherichia coli: possible roles of PBP 1b and PBP 3

Abstract: The two membrane precursors (pentapeptide lipids I and II) of peptidoglycan are present in Escherichia coli at cell copy numbers no higher than 700 and 2,000 respectively. Conditions were determined for an optimal accumulation of pentapeptide lipid II from UDP-MurNAc-pentapeptide in a cell-free system and for its isolation and purification. When UDP-MurNAc-tripeptide was used in the accumulation reaction, tripeptide lipid II was formed, and it was isolated and purified. Both lipids II were compared as substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
141
1
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(147 citation statements)
references
References 46 publications
4
141
1
1
Order By: Relevance
“…Therefore, in the presence of only one PAP2 C 55 -PP phosphatase, C 55 -PP and C 55 -P must be efficiently translocated across the inner membrane to reach the sites of dephosphorylation and glycosylation, respectively. This is supported by the fact that a high rate of transbilayer movement of C 55 -P was observed in Micrococcus lysodeikticus (43,44), which has to match the high rate of peptidoglycan synthesis (45). It was hypothesized that the long chain of the carrier lipid enables spontaneous diffusion of the latter across membranes (46).…”
Section: Discussionsupporting
confidence: 49%
“…Therefore, in the presence of only one PAP2 C 55 -PP phosphatase, C 55 -PP and C 55 -P must be efficiently translocated across the inner membrane to reach the sites of dephosphorylation and glycosylation, respectively. This is supported by the fact that a high rate of transbilayer movement of C 55 -P was observed in Micrococcus lysodeikticus (43,44), which has to match the high rate of peptidoglycan synthesis (45). It was hypothesized that the long chain of the carrier lipid enables spontaneous diffusion of the latter across membranes (46).…”
Section: Discussionsupporting
confidence: 49%
“…In the present work, we demonstrated that the D-lysine-containing UDPMurNAc-tripeptide was a good substrate for T. maritima MraY, as good as the conventional UDP-MurNAc-pentapeptide, yielding tripeptide lipid I (Table 3). Such a behavior is not unprecedented; in E. coli, the formation of tripeptide lipid II from UDP-MurNAc-tripeptide was reported in a cell-free system (33), implying that the meso-A 2 pm-containing UDP-MurNAc-tripeptide is a substrate for MraY (and MurG) from this species. Taking into account the usual lack of specificity of MurG and of the glycosyltransferases for the peptide part of the lipid intermediates, it is reasonable to consider that the D-lysine-containing tripeptide is incorporated into the peptidoglycan of T. maritima, as it is the case for the meso-A 2 pm-containing tripeptide into the peptidoglycan of E. coli (33).…”
Section: Discussionmentioning
confidence: 99%
“…The bifunctional nature of the high-molecular-weight PBPs 2 and 3 is still controversial. While the TPase activity of both proteins was proven, the GTase activity could not be demonstrated unambiguously [7]. PBP2 in conjunction with the RodA protein was shown to be involved in cell elongation; PBP3 together with the FtsW protein is believed to play an important role during cell septation [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%